(untitled) (Innovative professional education, 2023)
The article is devoted to the formation of environmental competence of future skilled workers of restaurant business establishments in the context of the implementation of the HACCP system principles in the educational and production process. A brief description of the principles of the HACCP system, which is intended for use by service market operators to prevent the occurrence of hazards associated with the storage, production and sale of culinary products, is given. In particular, attention is paid to the issue of production waste and garbage management - one of the key aspects of the HACCP system.